(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2018)
Educational reforms implemented in Poland between 2000 and 2016 changed the structure of post-middle school education. This has led to qualitative changes in education and determined local strategies for the development of education. Education can only keep up with economic and civilizational progress through effective investment. This can be achieved by providing an optimal educational structure in line with the current and future demand for work. The purpose of this study is to conduct an in-depth analysis of the structure of vocational and general education in Poland and to show how it has changed over the past 15 years. The study has been conducted using official data published in the reports Education (2006-2016) by the Central Statistical Office (GUS) and the Statistical Yearbooks of the Republic of Poland (2000-2016). The OECD Yearbook, Observer, Date and Stat Extracts databases have also been used. The results of the study have confirmed the thesis that the current fluctuations in the educational structure are detached from the real needs of the national economy implementing the plan of reducing the distance between Poland and the developed countries of the European Union. There are significant differences between the educational structures in individual provinces, which may have an impact on the effective stimulation of the development of social capital and, consequently, on the economic development of the country. The author points out the reasons why the educational structure in Poland does not conform to the needs of the national economy. By analysing changes in developed EU countries, he also presents his conclusions and proposals of how to adapt the educational structure to a knowledge-based economy.